2012
DOI: 10.6061/clinics/2012(11)11
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA exon 20 mutations are associated with poor prognosis in breast cancer patients

Abstract: OBJECTIVES:The phosphatidylinositol 3-kinase/AKT axis is an important cell-signaling pathway that mediates cell proliferation and survival, two biological processes that regulate malignant cell growth. The phosphatidylinositol 3-kinase CA gene encodes the p110α subunit of the phosphatidylinositol 3-kinase protein. There are phosphatidylinositol 3-kinase CA mutations in several types of human tumors, and they are frequently observed in breast cancer. However, these mutations have not been investigated in Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 22 publications
7
46
3
2
Order By: Relevance
“…TP53 and PIK3CA are not mutually exclusive at the observation of TCGA breast cancer data, which is concordant to the previous report [11]. Heatmap visualization of unsupervised clustering of pathway level characteristics shows distinguishing subgroup pattern between "TP53 mutated and PIK3CA non-mutated samples enriched" subgroup (D, E and F) and "TP53 non-mutated and PIK3CA mutated samples enriched" subgroup (A, B and C).…”
Section: Resultssupporting
confidence: 85%
“…TP53 and PIK3CA are not mutually exclusive at the observation of TCGA breast cancer data, which is concordant to the previous report [11]. Heatmap visualization of unsupervised clustering of pathway level characteristics shows distinguishing subgroup pattern between "TP53 mutated and PIK3CA non-mutated samples enriched" subgroup (D, E and F) and "TP53 non-mutated and PIK3CA mutated samples enriched" subgroup (A, B and C).…”
Section: Resultssupporting
confidence: 85%
“…In these studies, however, a cut point was set at a higher age, 50-55 years or menopause. [62][63][64] On the other hand, a trend towards association between PIK3CA somatic mutation in older patients was also already reported.…”
Section: Discussionmentioning
confidence: 94%
“…Not surprisingly, correlation studies between PI3K/Akt mutations and p53 mutations have also suggested conflicting patient outcome. Furthermore, PIK3CA mutations (exon 20) were recently reported to have a positive correlation with p53 mut in breast cancer [74], in direct contrast with the data presented by Boyault et al [72]. At the same time, the presence of high p53 expression (clinically interpreted as p53 mut ) in HER2 + breast tumours is associated with better outcome following trastuzumab treatment [73].…”
Section: Pi3k/akt and P53 Pathway Interactions: Clinical Implicationsmentioning
confidence: 99%